Genetic analysis of hypoxia tolerance and susceptibility in Drosophila and humans. - Zhou, D.; Haddad, G.G. (Annual Review of Genomics and Human Genetics, 2013)
Oxygen is essential for metazoans' life on earth. Oxygen deprivation, or hypoxia, contributes significantly to the pathophysiology of many human diseases. A better understanding of the fundamental molecular and genetic basis for adaptation to low-oxygen environments will help us develop therapeutic strategies to prevent or treat diseases that have hypoxia as a major part of their pathogenesis. Different cells and organisms have evolved different ways to cope with this life-threatening challenge, and the molecular and genetic mechanisms remain largely unknown. The current revolution of genomic technology has advanced our understanding of the genetic basis of many diseases and conditions, including hypoxia tolerance and susceptibility. In this review, we highlight the progress made in understanding the molecular responses to hypoxia in an animal model organism (Drosophila melanogaster) and genetic adaptation to high-altitude hypoxia in humans.